Technical Note: Company Risk-related Disclosures in a Code Law Country: A Synopsis - Jonas Oliveira; Lúcia Lima Rodrigues; Russell Craig (Australasian Accounting, Business and Finance Journal, 2013)
This synopsis provides a concise historical contextualisation of current risk disclosure issues, highlights major factors influencing contemporary risk reporting practices, and engages in a reflective overview of four recently published papers on aspects of corporate risk-related disclosures in a code law country, Portugal. The breadth and depth of our analysis is modest. Nonetheless we report findings indicating that risk-related disclosures are inadequate, lack transparency, and compound the difficulty of assessing the risk profile of a company. We contend that recent regulation initiatives have been of dubious effectiveness in improving the quality of risk information disclosed. In respect of the Portuguese context, we find that companies disclose risk-related information principally to reduce agency costs and to enhance corporate reputation. We contend that enhanced corporate accountability would be more likely to ensue if further disclosures of relevant risk-related information were mandated. One mechanism to do so would be through regulations recommended by the International Integrated Reporting Committee (IIRC).
Keywords: Risk; management; disclosures; visibility; reputation; agency; Portugal